RELEVANSI KONSEP MODERNISASI PERSPEKTIF IBNU KHALDUN TERHADAP PERENCANAAN PENDIDIKAN AGAMA ISLAM DI ERA KONTEMPORER - Febi Febrianda; Wedra Aprison (CV. ADIBA ASIHA AMIRA, 2025)
This research discusses the importance of the role of Islamic education in the modern era. The foundation of Islamic education, namely the Qur'an and Hadith, is the main reference for reform after renewal in the context of its implementation of the development of education in the Islamic world which continues to develop. In Indonesia itself, the implementation of national education is regulated in Law No. 20 concerning the National Education System. No less important, the reform is certainly inseparable from the role of Islamic figures who struggle through their thoughts so that Islamic education continues to go hand in hand and not be left behind even though the times continue to develop. The purpose of this research is specific to one of the figures of Islamic modernization, namely Ibn Khaldun. From his perspective, Ibn Khaldun gave criticism as well as improvement of the Islamic education system. In this context, Ibn Khaldun conveyed his ideas regarding the modernization of the educational process. In this study, Ibn Khaldun's thoughts on his views on the concept of modernization offered as a form of realization by the Indonesian nation itself as outlined in the National Education System Law, and also its implementation on the development of Islamic education in Indonesia. This type of research is included in qualitative research (library research) which examines a theoretical and in-depth study so that conclusions will be obtained. The results of this study show that there is a conformity between Ibn Khaldun's thinking views regarding the concept of modernization offered to its implementation in the management of the Islamic education system. Its relevance to the current Islamic education process is that Islamic education should not only be directed to theoretical understanding, but also need to be faced with social reality, systematic teaching materials, maturation of the foundation of Islamic values, so that a generation that is able to be competitive in Indonesia in today's modern world is born. Not only that, the thought of modernizing Islamic education offered by Ibn Khaldun also has an impact on the policies taken with the goals and values agreed upon in the regulations in accordance with the demands of the times.